Atomic structure of the regulatory TGS domain of Rel protein from Mycobacterium tuberculosis and its interaction with deacylated tRNA - Shin, Joon (2022)
The stringent response is critical for the survival of Mycobacterium tuberculosis (Mtb) under nutrient starvation. The mechanism is mediated by a GTP pyrophosphokinase known as Rel, containing N-terminal synthetase and hydrolase domains and C-terminal regulatory domains, which include the TGS domain (ThrRS, GTPase, and SpoT proteins) that has been proposed to activate the synthetase domain via interaction with deacylated tRNA. Here, we present the NMR solution structure of the Mtb Rel TGS domain (MtRel TGS), consisting of five antiparallel β-strands and one helix-loop-helix motif. The interaction of MtRel TGS with deacylated tRNA is shown, indicating the critical amino acids of MtRel TGS in tRNA binding, and presenting the first structural evidence of MtRel TGS binding to deacylated tRNA in solution in the absence of the translational machinery.